2016
DOI: 10.1080/09735070.2016.11905475
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Medication Adherence Among Women Living in Rural Areas Suffering from Hypertension: The Case of Dikgale-Communities

Abstract: Poor adherence to antihypertensive medications remains a significant challenge in the management of hypertension among women living in rural areas. The objective of the study was to assess the reasons of nonadherence in women suffering from hypertension. The researchers used a qualitative exploratory research design to conduct the study. A purposive sampling technique was used to select fifty (50) Black African women who participated in five ( 5) focus group interviews. The NVivo program was used to manage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
7
2
Order By: Relevance
“…Healthy diet comprising fruits and vegetables was unaffordable. This is similar to a recent study in a low income country [21]. Smoking was present in only a few.…”
Section: Qualitative Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Healthy diet comprising fruits and vegetables was unaffordable. This is similar to a recent study in a low income country [21]. Smoking was present in only a few.…”
Section: Qualitative Resultssupporting
confidence: 92%
“…The present study, thus, highlights the importance of poor patient access, health education and empowerment, and financial support at patient level and greater use of low-cost generics and combination therapies by the physicians. A systemwide change in healthcare delivery in India [21] is needed to control the epidemic of hypertension related diseases in India and other low and lower-middle income countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant relationship between marital status and adherence, which is similar to a study conducted in Ghana and Nigeria [9]. The lack of any statistical significant association between claimed adherence and the period on treatment, reminder (help) to take their medication by either a family member or friend, as well as perceptions and beliefs about hypertension and its treatment, are different from studies previously conducted in South Africa [37,56] as well as wider [1]. The results also differ from studies conducted in Namibia and Nigeria, which reported that patients with good family support or social support from friends had better adherence than those without [30,57,58].…”
Section: Discussioncontrasting
confidence: 46%
“…Furthermore, psychosocial factors also influence medication adherence, such as depressed emotion, perceived severity of disease, self-rated health, perceived symptoms, and self-efficacy (Al-Noumani et al, 2018; Asgari et al, 2019). Knowledge of hypertension and patients’ literacy (Boima et al, 2015; Shirindi et al, 2016; Pan et al, 2017) were also found to be predictors of medication adherence. There have been interventions and measures pertinent to hypertensive patients’ adherence improvement, and certain interventions have been confirmed to be effective.…”
Section: Introductionmentioning
confidence: 94%